Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3109/10826084.2016.1155603
|View full text |Cite
|
Sign up to set email alerts
|

School Factors and Alcohol Use: The Moderating Effect of Nativity in a National Sample of Latino Adolescents

Abstract: School connectedness is a contemporaneous risk factor for alcohol use among those born in the United States. Prevention efforts that address school contextual factors may be important for all Latino students to reduce engagement in alcohol use and optimize well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…For example, with respect to internalizing problems, youth born in Mexico (vs. the United States) have not only steeper decreases in depression from Ages 10 to 18 (Cruz et al, 2021) but also higher rates of social anxiety and loneliness between the Ages 11 and 15 (Polo & Lo ´pez, 2009), which may be reflected in the development of neuroticism. In the externalizing domain, studies have found that high-school-aged youth born in Mexico (vs. the United States) have lower rates of substance use (Prado et al, 2009;Vaughan et al, 2016), which may be reflected in the development of conscientiousness. However, other studies suggest that nativity does not affect development within these domains (e.g., see Aizpitarte et al, 2019;Gonzales et al, 2017).…”
Section: Generalizability Versus Culture-specificity Of Personality T...mentioning
confidence: 99%
“…For example, with respect to internalizing problems, youth born in Mexico (vs. the United States) have not only steeper decreases in depression from Ages 10 to 18 (Cruz et al, 2021) but also higher rates of social anxiety and loneliness between the Ages 11 and 15 (Polo & Lo ´pez, 2009), which may be reflected in the development of neuroticism. In the externalizing domain, studies have found that high-school-aged youth born in Mexico (vs. the United States) have lower rates of substance use (Prado et al, 2009;Vaughan et al, 2016), which may be reflected in the development of conscientiousness. However, other studies suggest that nativity does not affect development within these domains (e.g., see Aizpitarte et al, 2019;Gonzales et al, 2017).…”
Section: Generalizability Versus Culture-specificity Of Personality T...mentioning
confidence: 99%
“…Early alcohol and tobacco use has been linked to many adverse risks such as delinquency, lower academic achievement (Schofield et al, 2015; Vaughan et al, 2016), risky sexual behavior (Stueve & O’Donnell, 2005), and socializing with other substance-using peers which can facilitate and markedly escalate deviant behavior (West et al, 2013). Early age drinking and smoking has also been found to increase later-in-life risk of substance abuse and addiction (Gil et al, 2004).…”
mentioning
confidence: 99%